Evaluation of Dietary Calcium Level and Fat Source on Growth Performance and Mineral Utilization of Heat-distressed Broilers - Smith, M.O.; Soisuvan, K.; Miller, L.C. (International Journal of Poultry Science, 2002)
Male broilers (commercial strain) were used to evaluate the effects of diets differing in fat source on performance of heat-distressed broilers. Dietary treatments included corn oil (CO), animal fat (AF), fish oil (FO) and a dry blended (animal and vegetable) fat product (DB) at either 0.9 or 1.5 % calcium. Diets were isocaloric with each containing an equal number of calories from fats. Birds were reared in floor brooder pens and fed experimental diets from Day 1 to 21 and then assigned the same dietary treatments in one of two environmentally controlled chambers. One chamber was maintained at 23.9 °C, whereas birds in the second chamber were exposed to 8 hours of 23.9 °C, 4 hours of 23.9 to 35 °C, 4 hours of 35 °C and 8 hours of 35 to 23.9 °C. At 42 days of age, plasma concentration of calcium and magnesium were higher (p > 0.01) in heat distressed (HD) birds than in their thermoneutral (TN) counterparts. Dietary calcium level, but not fat source, affected plasma calcium concentration. Temperature significantly (p < 0.05) affected the relative mineral retention (feed minus fecal mineral content) of magnesium while relative mineral retention of copper was affected by fat source. There was no effect of calcium level on performance but HD birds gained 31 % less weight than TN. Birds fed AF gained 10 % more than FO and 14 % more than DB. Data suggest that both fat source and environmental temperature influence mineral utilization and body weight gain.